2015
DOI: 10.1007/s13566-015-0199-2
|View full text |Cite
|
Sign up to set email alerts
|

High-grade prostate adenocarcinoma (Gleason Score ≥8): survival and disease control following radical prostatectomy versus radiotherapy plus long-course hormone therapy

Abstract: Objective The optimal primary intervention for treatment of clinically localized high-grade prostate cancer remains to be identified. The present investigation compares disease control in patients treated with primary radical prostatectomy (RP) versus radiotherapy (RT). Methods Eligible patients were identified by Gleason 8-10 prostate adenocarcinoma at biopsy between 2003 and 2010, treated with either primary RP or RT. Patients with PSA ≥30 or clinically evident seminal vesicle or lymph node involvement at di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
2
2

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 24 publications
(40 reference statements)
0
2
2
Order By: Relevance
“…RT with 2-3 years of ADT is now a NCCN category 1 recommendation for patients with a high-risk of recurrence [ 1 ] based on randomized trial data showing decreased rates of clinical progression and increased overall survival compared to patients not receiving ADT [ 17 ]. A more recent study by Watkins et al reported markedly higher 5-year BF rates of 79.4% for RP and 25.2% for RT + ADT, compared to the current study, and did not report metastatic outcomes [ 16 ]. These results are likely due a lower percentage of RP patients receiving adjuvant RT and a difference in the definition of BF for patients receiving salvage RT [ 16 ].…”
Section: Discussioncontrasting
confidence: 78%
See 3 more Smart Citations
“…RT with 2-3 years of ADT is now a NCCN category 1 recommendation for patients with a high-risk of recurrence [ 1 ] based on randomized trial data showing decreased rates of clinical progression and increased overall survival compared to patients not receiving ADT [ 17 ]. A more recent study by Watkins et al reported markedly higher 5-year BF rates of 79.4% for RP and 25.2% for RT + ADT, compared to the current study, and did not report metastatic outcomes [ 16 ]. These results are likely due a lower percentage of RP patients receiving adjuvant RT and a difference in the definition of BF for patients receiving salvage RT [ 16 ].…”
Section: Discussioncontrasting
confidence: 78%
“…A more recent study by Watkins et al reported markedly higher 5-year BF rates of 79.4% for RP and 25.2% for RT + ADT, compared to the current study, and did not report metastatic outcomes [ 16 ]. These results are likely due a lower percentage of RP patients receiving adjuvant RT and a difference in the definition of BF for patients receiving salvage RT [ 16 ]. In contrast to the study by Watkins et al, patients in our study that received salvage RT were not scored as BF unless they experienced PSA relapse after completion of RT [ 16 ].…”
Section: Discussioncontrasting
confidence: 78%
See 2 more Smart Citations